miR-30a attenuates cardiac fibrosis in rats with myocardial infarction by inhibiting CTGF - Chen, Liwen (Exp Ther Med, 2018)
The mechanism of miR-30a in myocardial fibrosis in rats with myocardial infarction (MI) was investigated. rAAV9-miR-30a was constructed and transfected to heart via injecting into the left ventricular cavity of MI rats. The sham operation group, control group, miR-30a group and miR-30a-NC group were established. Besides, the 3′-UTR of CTGF was inserted into luciferase expression plasmid (pMir-report), then transfected into COS1 cells. miR-30a and control miRNA were, respectively, cotransfected into COS1 cells. The expression of luciferase was detected before and after knockdown of the binding site of miR-30a and the 3′-UTR of CTGF. Four weeks after MI surgery, cardiac function was measured by color Doppler echocardiography, including short axis shortening (FS) and left ventricular ejection fraction (LVEF); the myocardial collagen volume fraction (CVF) was observed by Masson's staining; deposition of collagen I and collagen III were evaluated by immunohistochemical stain; using real-time PCR to detect expression levels of miR-30a and CTGF; the expression of CTGF was observed by western blotting. In MI group, cardiac function was significantly improved, while the expression levels of CVF, collagen I and III, the ratio of type I/III collagen, CTGF were significantly reduced. After knockdown the binding site of miR-30a and the 3′-UTR of CTGF, luciferase expression in COS1 cells decreased significantly. miR-30a might inhibit the expression of CTGF by directly combining with the 3′-UTR site of CTGF after MI, thereby reduce the production of collagen in myocardia, inhibit myocardial fibrosis, then improve cardiac function.